Comics : a global history, 1968 to the present - Mazur, Dan, 1959-; Danner, Alexander (London : Thames & Hudson, 2014)
This is the first global history of comics around the world from the late 1960s to the present day. Comics, manga, bandes dessinées, fumetti, tebeo, historietas, no matter the name, they have been a powerful medium across four continents for decades. This is the history of comics around the world from the late 1960s to the dawn of the 21st century. This is a richly illustrated narrative of extraordinary scope. Examples from all over the world include everything from Crumb and Kirby to RAW; from Metal Hurlant to Marjane Satrapi to nouvelle manga; from both the American mainstream and underground to the evolving and influential British scene. The images here are bright and colorful, dark and brooding, arresting and pleasant, all at the same time. The authors are the first to write a broadly comprehensive history of this most accessible, democratic, and occasionally subversive modern popular art form, displaying an intimate familiarity with schools and styles, writers, artists, and companies across countries and generations. In showing us both post-apocalyptic dreamscapes and portraits of the everyday, this book looks at this thirty-plus year period through a very unique lens.
Part 1. 1968-1978. The undergrounds and after -- American mainstream comics -- American mainstream comics : a new generation -- Mainstream manga -- Garo and alternative manga -- Tezuka -- L'age adulte in Bande dessinée and other European comics -- The new European publishing -- Part 2. 1978-1990. À suivre and the wild invasion -- New trends in Italian and Spanish comics -- Mainstream rebels in the U.S. and U.K. -- The dawn of the graphic novel, the Raw generation and punk comix -- The growth of realism in manga -- Part 3. 1990 onward. American mainstream comics in the 1990s -- American alternative comics of the 1990s -- European comics in the 1990s -- The quest for "respectable" manga -- Comics in the twenty-first century : an international art form -- New forms, new technologies, new audiences.
"289 illustrations in color and black and white."
boek
Keywords: Comic books, strips, etc. -- History and criticism; Graphic novels -- History and criticism; Comic strip characters -- History; Comic books, strips, etc; Comic strip characters; Graphic novels; Criticism, interpretation, etc; History